CDERA : cartographie des risques aux Cara - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Terry Ally relate les travaux de la CDERA (Caribbean Disaster Emergency Agency), l’agence cara